Boron doped nanostructure ZnO films onto ITO substrate - Caglar, Mujdat; Ilican, Saliha; Caglar, Yasemin; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2011)
Undoped and boron (B) doped nanostructure ZnO films were prepared by sol-gel method using spin coating technique. The effects of B content on the crystallinity and morphological properties of ZnO films were analyzed by X-ray diffractometer, field emisison scanning electron microscopy (FESEM) and atomic force microscopy (AFM). X-ray diffraction (XRD) patterns confirm the hexagonal wurtzite type polycrystalline structure of the films and the incorporation of boron leads to substantial changes in the structural characteristics of ZnO films. The FESEM and AFM measurements indicated that the surface morphology of the films was affected from the boron incorporation. The absorption spectra revealed that B doped ZnO films had a optical band gap exhibiting directly optical transtions and optical band gap of the films decreased with the increase in temperature. The electrical conductivity dependence of temperature of the 5% boron doped nanostructure ZnO film revealed that the conduction mechanism of the film was an extrinsic conductivity mechanism with shallow and deep trap levels. At higher electric fields, the conductivity mechanism of the film was controlled by space charge limited current mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: B doped ZnO; Sol-gel; Nanostructure film; Activation energy; Space charge limited current